Design of Web-Based Digital Mail Services Using Prototyping Method - Sari, Renny Puspita; Febriyanto, Ferdy; Rahmayuda, Syahru (Sebatik, 2025)
Information technology at the village office level is important in supporting the modernization and optimization of public services. However, the administrative process, especially correspondence services in the village office, especially in Mekar Baru village, is still mostly done manually, which results in delays, inefficiencies, and potential recording errors. These limitations often make it difficult for residents to access correspondence services that require optimal services. To overcome these problems, a web-based digital letter service is needed to quickly, accurately, and well-documented support the letter management process. It allows villagers to create letters independently without coming directly to the village office by providing online services via computers or smartphones. In designing this digital letter service, the prototyping method is applied because it provides an iterative and collaborative system development approach that can accommodate user input at each stage of development so that the resulting system is more in line with user needs and expectations. The research stages include needs analysis, initial prototype creation, testing, and prototype refinement based on user feedback. The initial prototype is then developed and tested through black box testing to ensure the suitability of system functionality and detect errors in system logic. The result of this research is a prototype of a digital mail service website with features of Mekar Baru village information, an independent letter-making by residents, and integrated digital archiving. This system is designed to facilitate access to correspondence services for Mekar Baru village residents and reduce the administrative burden of Mekar Baru village office staff.